A comparative observational study on intrasphincteric injections with Botulinum toxin vs. enteral neuromodulation in chronic refractory constipation - Walther, Mona; Müller, Hanna; Weiß, Christel; Carbon, Roman; Diez, Sonja; Besendörfer, Manuel (BMC Pediatrics, 2023)
Purpose: Botulinum toxin injections in the anal sphincter apparatus (Botox) and enteral neuromodulation (ENM) are options for treatment of refractory chronic constipation. We present a retrospective comparative observational study. Patients and methods: From 2014 to 2022, pediatric patients with chronic constipation were either treated with Botox or ENM with continuation of conservative treatment. Comparison was conducted regarding the primary outcome variables defecation frequency, stool consistency, and abdominal pain. Secondary outcomes were fecal incontinence, enuresis, change of medication and safety of treatment. Results: 19 Botox patients (10 boys, 9 girls, 12 patients with Hirschsprung disease (HD), 7 patients with functional constipation (FC)) were compared to 24 ENM patients (18 boys, 6 girls, 12 HD patients, 7 FC patients). Groups differed significantly in age (5.0 years (Botulinum toxin) and 6.5 years (ENM), mean values, p-value 0.008). Improvement of constipation was seen in 68% (n = 13/19) of Botox and 88% (n = 21/24) of ENM patients (p = 0.153). Influence of etiology on therapeutic effects was not observed. Complications were minor. Conclusions: Botox and ENM can be considered as valuable and effective treatment options in refractory chronic constipation. Prospective, large-population studies should be designed to enable improved evidence.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Botulinum toxin; Chronic refractory constipation; Enteral neuromodulation; Fecal incontinence; Hirschsprung disease

ARID1B-related disorder in 87 adults: Natural history and self-sustainability - van der Sluijs, P. J.; Gösgens, M.; Dingemans, A. J.M.; Striano, P.; Riva, A.; Mignot, C.; Faudet, A.; Vasileiou, Georgia; Walther, Mona; Schrier Vergano, S. A.; Alders, M.; Alkuraya, F. S.; et al. (Genetics in Medicine Open, 2024)
Purpose: ARID1B is one of the most frequently mutated genes in intellectual disability cohorts. Thus, far few adult-aged patients with ARID1B-related disorder have been described, which limits our understanding of the disease's natural history and our ability to counsel patients and their families. Methods: Data on patients aged 18+ years with ARID1B-related disorder were collected through an online questionnaire completed by clinicians and parents. Results: Eighty-seven adult patients with ARID1B were included. Cognitive functioning ranged from borderline to severe intellectual disability. Patients identified through the genetic workup of their child were either mosaic or had a variant in exon 1. New clinical features identified in this population are loss of skill (16/64, 25%) and recurrent patella luxation (12/45, 32%). Self-sustainability data showed that 88% (45/51) could eat independently, and 16% (7/45) could travel alone by public transport. Facial photo analysis showed that patients’ photographs taken at different ages clustered consistently, separate from matched controls. Conclusion: The ARID1B spectrum is broad, and as patients age, there is a significant shift in the medical aspects requiring attention. To address the changing medical needs with increasing age, we have formulated recommendations to promote timely intervention in an attempt to mitigate disease progression.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Adult; ARID1B; Coffin–Siris syndrome; Developmental delay; Intellectual disability

Delineation of the adult phenotype of Coffin–Siris syndrome in 35 individuals - Schmetz, Ariane; Lüdecke, Hermann Josef; Surowy, Harald; Sivalingam, Sugirtahn; Bruel, Ange Line; Caumes, Roseline; Charles, Perrine; Chatron, Nicolas; Chrzanowska, Krystyna; Codina-Solà, Marta; Colson, Cindy; Cuscó, Ivon; et al. (Human genetics, 2023)
Coffin–Siris syndrome (CSS) is a rare multisystemic autosomal dominant disorder. Since 2012, alterations in genes of the SWI/SNF complex were identified as the molecular basis of CSS, studying largely pediatric cohorts. Therefore, there is a lack of information on the phenotype in adulthood, particularly on the clinical outcome in adulthood and associated risks. In an international collaborative effort, data from 35 individuals ≥ 18 years with a molecularly ascertained CSS diagnosis (variants in ARID1B, ARID2, SMARCA4, SMARCB1, SMARCC2, SMARCE1, SOX11, BICRA) using a comprehensive questionnaire was collected. Our results indicate that overweight and obesity are frequent in adults with CSS. Visual impairment, scoliosis, and behavioral anomalies are more prevalent than in published pediatric or mixed cohorts. Cognitive outcomes range from profound intellectual disability (ID) to low normal IQ, with most individuals having moderate ID. The present study describes the first exclusively adult cohort of CSS individuals. We were able to delineate some features of CSS that develop over time and have therefore been underrepresented in previously reported largely pediatric cohorts, and provide recommendations for follow-up.
CRIS-Team Scopus Importer:2023-12-29

The missing link: ARID1B non-truncating variants causing Coffin-Siris syndrome due to protein aggregation - Bosch, Elisabeth; Güse, Esther; Kirchner, Philipp; Winterpacht, Andreas; Walther, Mona; Alders, Marielle; Kerkhof, Jennifer; Ekici, Arif Bülent; Sticht, Heinrich; Sadikovic, Bekim; Reis, André; Vasileiou, Georgia (Human genetics, 2024)
ARID1B is the most frequently mutated gene in Coffin-Siris syndrome (CSS). To date, the vast majority of causative variants reported in ARID1B are truncating, leading to nonsense-mediated mRNA decay. In the absence of experimental data, only few ARID1B amino acid substitutions have been classified as pathogenic, mainly based on clinical data and their de novo occurrence, while most others are currently interpreted as variants of unknown significance. The present study substantiates the pathogenesis of ARID1B non-truncating/NMD-escaping variants located in the SMARCA4-interacting EHD2 and DNA-binding ARID domains. Overexpression assays in cell lines revealed that the majority of EHD2 variants lead to protein misfolding and formation of cytoplasmic aggresomes surrounded by vimentin cage-like structures and co-localizing with the microtubule organisation center. ARID domain variants exhibited not only aggresomes, but also nuclear aggregates, demonstrating robust pathological effects. Protein levels were not compromised, as shown by quantitative western blot analysis. In silico structural analysis predicted the exposure of amylogenic segments in both domains due to the nearby variants, likely causing this aggregation. Genome-wide transcriptome and methylation analysis in affected individuals revealed expression and methylome patterns consistent with those of the pathogenic haploinsufficiency ARID1B alterations in CSS cases. These results further support pathogenicity and indicate two approaches for disambiguation of such variants in everyday practice. The few affected individuals harbouring EHD2 non-truncating variants described to date exhibit mild CSS clinical traits. In summary, this study paves the way for the re-evaluation of previously unclear ARID1B non-truncating variants and opens a new era in CSS genetic diagnosis.
CRIS-Team Scopus Importer:2024-07-26